Streamlining library services : what we do, how much time it takes, what it costs, how we can do it better - Dougherty, Richard M. (Scarecrow Press, 2008)
"Streamlining Library Services provides information on how to diagnose problem areas using such tools as Pareto and fishbone charts; use brainstorming; organize a work-flow study; and build and present cost studies. Special emphasis is placed on activities that should occur after the analysis is concluded, including data analysis, study results, and making recommendations to management. Guidelines are provided for managers and staff as they strive to streamline activities. Topics include implementation issues and strategies that must be addressed as new workflows and services are introduced, and organizational change issues and strategies for building staff support toward change."--Book jacket.